Evaluación del impacto del rebranding en la percepción de los clientes de la Cooperativa de Ahorro y Crédito Cacpe Loja en el cantón Loja, durante el período 2022. - Montoya Montoya, María de los Ángeles (2024)
Cooperativa de Ahorro y Crédito Cacpe Loja has carried out a rebranding process of its corporate identity to adapt to changes in the financial sector. The objective of this study is to evaluate the impact of the rebranding on the perception of the clients of this cooperative, located in the province of Loja, canton Loja. Since 1991, it has been offering financial services, and in 2022, it renewed its corporate identity, implementing significant changes. To achieve the objectives of this research, a mixed methodological approach was used, combining qualitative and quantitative techniques. The main techniques used were the survey and the interview. A sample of 378 people was selected from the 22,564 active members of the cooperative. Surveys were conducted through Google Forms to assess customer impact and satisfaction, and interviews were conducted to understand the rebranding process and strategies. The results show a high level of satisfaction and acceptance of the new image, with a remarkable level of loyalty to the cooperative: 55% of respondents have been customers for more than six years, and 77% of members reported feeling extremely satisfied with the cooperative after the rebranding process. It is concluded that the rebranding strategies were successful, modernizing and better reflecting the company's corporate identity. Key words: rebranding; customer perception; corporate identity; financial marketing; business strategies.